2016
DOI: 10.3171/2016.7.focus16218
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging–guided laser interstitial thermal therapy for previously treated hypothalamic hamartomas

Abstract: OBJECTIVE Hypothalamic hamartomas (HHs) are associated with gelastic seizures and the development of medically refractory epilepsy. Magnetic resonance imaging–guided laser interstitial thermal therapy (MRg-LITT) is a minimally invasive ablative treatment that may have applicability for these deep-seated lesions. Here, the authors describe 3 patients with refractory HHs who they treated with MRg-LITT. METHODS Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…Régis et al published a prospective series of 57 patients with HH treated with GK with a 3‐year follow‐up in 48 of them and a range of age from 3 to 50 years. Good result (Engel class I or II) was achieved in 68.8% of the patients in terms of seizure control and none of the patients showed cognitive decline or disabling endocrinological deficits after treatment (Burrows et al, ). The latest surgical approach for HH associated with refractory epilepsy is the magnetic resonance imaging‐guided laser interstitial thermal therapy (MRg‐LITT), which offers the advantage of real‐time imaging of direct thermal ablation with minimal major surgical complications (Du, Gandhi, Rekate, & Mehta, ).…”
Section: Discussionmentioning
confidence: 99%
“…Régis et al published a prospective series of 57 patients with HH treated with GK with a 3‐year follow‐up in 48 of them and a range of age from 3 to 50 years. Good result (Engel class I or II) was achieved in 68.8% of the patients in terms of seizure control and none of the patients showed cognitive decline or disabling endocrinological deficits after treatment (Burrows et al, ). The latest surgical approach for HH associated with refractory epilepsy is the magnetic resonance imaging‐guided laser interstitial thermal therapy (MRg‐LITT), which offers the advantage of real‐time imaging of direct thermal ablation with minimal major surgical complications (Du, Gandhi, Rekate, & Mehta, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that disconnection of the lesion from the epileptogenic network is important, and often sufficient to resolve seizures rather than complete ablation or resection of the lesion itself. Burrows et al reported three cases of patients with decades of refractory symptoms after initial presentation in childhood who had undergone resection or radiosurgery previously, of which one was seizure free and one had meaningful reduction in seizure frequency [36].…”
Section: Hypothalamic Hamartomamentioning
confidence: 99%
“…In the early 2010s, new stereotactic thermocoagulation methods using magnetic resonance (MR) guidance such as highly focused ultrasound (HIFU) and laser interstitial (LITE) thermocoagulation were introduced to the field of functional neurosurgery and tested for the treatment of HH. No series of HIFU for HH has been published to date.…”
Section: Key Publications (In Chronologic Order) Studying Surgical Oumentioning
confidence: 99%
“…The fact that no destructive effect is observed in most of the patients after radiosurgery 36,37 may explain why no memory deficits have been found (even with long-term follow-up) after radiosurgery despite the use of a battery of standardized neuropsychological tests exploring intelligence and memory (immediate and delayed verbal and visual memory). 29 In the early 2010s, new stereotactic thermocoagulation methods using magnetic resonance (MR) guidance such as highly focused ultrasound (HIFU) and laser interstitial (LITE) 38 thermocoagulation were introduced to the field of functional neurosurgery and tested for the treatment of HH. No series of HIFU for HH has been published to date.…”
mentioning
confidence: 99%